Effect of Moisture Content and Machine Speed on Stripping Characteristics of Green Bengal Gram Pod Stripper - Singh, Daya S; Singh, Mohan (Journal of Agricultural Engineering, 2006)
Experiments were conducted to optimize the plant moisture content and speed of the machine optimal stripping efficiency and capacity of the developed fresh bengal gram pod stripping machine. The maximum efficiency of the machine was found to be 98.82% at 350 rpm of the machine and 61.41% plant moisture content (wb). The capacity of the machine corresponding to maximum efficiency was found to be 118.68 kg/h.